Vocabulary learning strategies: perspectives of Arabic language learners - Md Azmi, Afiqah; Mustapha, Nik Hanan; Khalil, 'Ammar (Universiti Sultan Zainal Abidin, 2025)
Ongoing discussions about enhancing students’ vocabulary mastery in learning foreign languages have spurred an urgent need for practicing vocabulary learning strategies (VLS) in learning new vocabulary. VLS are widely used as an effective learning tool, offering various advantages in vocabulary mastery. However, the empirical evidence supporting its implementation in the context of learning Arabic as a foreign language (AFL) remains limited. Therefore, this study aims to investigate the level of VLS implementation among Arabic foreign language learners. To gather quantitative data, survey research is employed using a VLS questionnaire developed by Gu (2018) with a 5-point Likert scale. This questionnaire was administered to diploma students majoring in Islamic Studies at Universiti Islam Antarabangsa Tuanku Syed Sirajuddin (UniSIRAJ), Malaysia. The data collected from 144 respondents were analyzed using SPSS. The results of the study indicate that the level of using VLS among the respondents is high, showing that they are active-users of VLS, whereas note-taking strategy is the most preferred, while inferencing strategy is the least used. Pedagogical implications of this study are that the implementation of VLS in the AFL context should be improved to enhance students’ Arabic vocabulary mastery